Promoting Open Educational Resources from Public Universities - Chiarani, Marcela Cristina (Universidad Nacional de Córdoba, Faculdad de Ciencias Sociales, Centro de Estudios Avanzados. Maestría en Procesos Educativos Mediados por Tecnología, 2016)
The Open Educational Resources Movement considers knowledge as a common good, and encourages teachers, researchers and autodidacts to distribute their own material produced in the Internet, under open-access licenses so that it can be reused, redistributed, combined and adapted. The objective of this article is to present the actions that the Area of Educational Technology (Technology Department from the Faculty of Mathematics, Physics and Natural Sciences at the National University of San Luis) has conducted in relation to Open Educational Resources (OER). The article starts with an introduction to concepts related to open access, OERs and open licenses. It also presents the actions that were carried out in order to conform to the OER movement initiatives related to teaching, research and extension tasks. Finally, we include conclusions and future challenges.